PROSES MORFOLOGIS PROSES MORFOLOGIS PEMBENTUKAN JAMAK NOMINA DALAM BAHASA ARAB - MOCHAMMAD SYAFIUDDIN SHOBIRIN (JoEMS (Journal of Education and Management Studies), 2020)
Arabic is a language that has the complexity of grammatical structure, especially in terms of morphology or Arabic scientific terms known as shorof science. Is a language study that focuses on the formation of words. One of the formation of words in Arabic that is quite complex is the formation of plural. This paper will try to review how the word changes from the singular (mufrad) to the plural. In accordance with the rules in Sharaf science, there are three plural forms, namely plural mudzakkar salim, plural salim muannats, and plural appraisers. The process of plural formation in nouns occurs from a single form that experiences affixation, impregnation, and changes in vocal structure. The plural mudzakkar salim is formed through the process of affixation by adding suffixes in the form of wawu-nun or ya'-nun. In addition, the formation of plural mudzakkar salim is not only due to morphological changes, but also due to syntactic processes. Whereas in the plural muannats the process is only by giving a suffix in the form of alif-ta '. Finally, the plural assessors undergo fairly complex morphological processes, because their formation is irregular and has 39 patterns. This process of tanning involves changing the vocal model to a single form, sometimes through affixation or adding consonants, and sometimes also through consonant dissipation and changes in vowel sound. But basically, these appraisals are sourced from sama’iy.